2010
DOI: 10.1002/mas.20287
|View full text |Cite
|
Sign up to set email alerts
|

Sample preparation methods for MALDI‐MS profiling of bacteria

Abstract: Direct matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) bacterial cell or lysate analysis appears to meet all the criteria required for a rapid and reliable analytical microorganism identification and taxonomical classification tool. Few-minute analytical procedure providing information extending up to sub-species level underlines the potential of the MALDI-MS profiling in comparison with other methods employed in the field. However, the quality of MALDI-MS profiles and consequently the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 134 publications
(231 reference statements)
1
53
0
1
Order By: Relevance
“…The optimal bacterial densities for MALDI-TOF MS have previously been reported as 4 mg cells per 30 mL 51 or 10 6 and 10 7 cells per mL. 48,52 In the present study, we found the optimal bacterial density as ca. 10 7 cells per mL, indicating that, to some extent, the cell density is flexible for MALDI lipid profiling.…”
Section: Effects Of Experimental Conditions On Lipid Profilingsupporting
confidence: 65%
“…The optimal bacterial densities for MALDI-TOF MS have previously been reported as 4 mg cells per 30 mL 51 or 10 6 and 10 7 cells per mL. 48,52 In the present study, we found the optimal bacterial density as ca. 10 7 cells per mL, indicating that, to some extent, the cell density is flexible for MALDI lipid profiling.…”
Section: Effects Of Experimental Conditions On Lipid Profilingsupporting
confidence: 65%
“…MALDI-TOF MS promises to be a fast, reliable, and cost-effective alternative to currently used methods (4,6,8). Apart from the species coverage of the reference database and the identification algorithm of the software (9,10), the sample preparation procedure seems to be critical for the performance of the system (11)(12)(13). Most studies evaluating the Bruker MALDI-TOF MS system used a direct transfer protocol, measuring whole bacterial cells prepared directly from freshly grown colonies.…”
mentioning
confidence: 99%
“…With this respect, several technological approaches have been proposed, such as accurate protocols standardization, bio-inspired bacteria purification systems, coupling with separative techniques, high-resolution MS methods, and bioinformatic tools [92][93][94][95]. Employing the pathogenic bacteria E. coli O157:H7 and Yersinia enterocolitica and the non-pathogenic E. coli MC1061 strain as model samples, we recently proposed the use of chemometric tools to extract relevant information, useful for comparing the fingerprint MALDI-TOF spectra of unknown bacteria with a spectral library, to accomplish robust bacteria identification and classification [96].…”
Section: Mass Spectrometrymentioning
confidence: 99%